Prevalence of Oral Candidiasis among Children Caused by Different Candida Species (Medicine Today, 2022)
Introduction: Oral candidiasis, which is caused by Candida species by the involvement of hard and soft palates, tongue, buccal mucosa, and floor of the mouth, is becoming a very common threat to oral health. Although in the majority of the cases, this infection is caused by Candida albicans which is a normal commensal organism in humans, however, it might be also caused by other Candida species, such as C. glabrata, C. tropicalis, and C. krusei.Objectives: This study aimed to evaluate the prevalence of oral candidiasis among children and to compare the type of causative candida species among them.Materials and Methods: This prospective observational study was conducted in the Shishu Hospital, Shamoly, Dhaka, spanned January 2016 through December 2016. A total of 286 oral swab samples were collected, and three methods including direct wet mount smear, staining, and culture were used for laboratory investigation of Candida infections.Results: Among 286 respondents, 161 (56.29%) were culturally and microscopically confirmed to have oral candidiasis. Among all of the detected species, C. Albicans was by far the highest species with 139(86.34%) followed by C. tropicalis with 14 (8.68%). Whereas 05(3.12%) cases were infected by C. krusei. On the other hand, the least detected species were C. glabrata and C. guilliermondii with 01(0.62%) and 02(1.24%) respectively.Conclusion: These days accurate and prompt identification of the infectious candida strains is crucial because isolates of Candida species differ extremely, both in their ability to produce infection and also in their susceptibility to antifungal agents.Medicine Today 2022 Vol.34(1): 57-60